Strategi Pembelajaran Dengan Memadukan Teknologi Dan Media - Linda, Linda (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
A learning strategy is a plan for a series of activities designed to achieve specific educational goals. In this context, a learning strategy is an activity that must be carried out by teachers and students. This is because a learning strategy is also defined as a set of learning materials and procedures to produce learning outcomes in students. The components that make up learning technology include television, film, overhead projectors, computers, and other hardware and software components. These findings reveal that learning media are communication tools in print or audio-visual form, including hardware technology. From the three opinions above, it can be concluded that learning media is anything that can convey messages, can stimulate the thoughts, feelings, and desires of students, thereby encouraging the creation of the learning process in students.